ADVANCES IN SERVERLESS COMPUTING: A PARADIGM SHIFT IN CLOUD APPLICATION DEVELOPMENT - Mohammed Khaja Sirajuddin (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
Serverless computing has emerged as a revolutionary paradigm in cloud computing, fundamentally transforming the landscape of application development and deployment. This comprehensive article examines the multifaceted impact of serverless architectures, exploring their technical foundations, economic implications, and operational benefits in modern cloud environments. The article delves into the core components of serverless computing, including event-driven architectures, automated scaling mechanisms, and resource allocation systems, while analyzing their collective impact on application development and deployment strategies. Through detailed examination of cost optimization models, development practices, and security considerations, this paper demonstrates how serverless computing addresses traditional cloud computing challenges while introducing new opportunities for innovation. The article analysis extends to emerging trends and future directions, highlighting the technology's potential to revolutionize cloud application development further. The article indicates that serverless computing represents not just a technological advancement but a fundamental shift in how organizations approach software development, offering improved developer productivity, reduced operational overhead, and enhanced scalability. This article contributes to the growing body of knowledge on cloud computing architectures while providing valuable insights for practitioners and researchers in the field.